2013
DOI: 10.1002/ejlt.201200239
|View full text |Cite
|
Sign up to set email alerts
|

From coffee industry waste materials to skin‐friendly products with improved skin fat levels

Abstract: Spent coffee grounds (SCG), which are the residue obtained from the treatment of coffee with hot water or steam, can be used for industrial applications, due to the high content in lipids. The cosmetic products might be a suitable application for these types of residues because the barrier properties of the stratum corneum (SC) are largely dependent on the intactness of the lipid lamellae that surrounds the corneocytes. The purpose of this work was to assess the feasibility of using the lipid fraction of SCG e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 22 publications
3
43
0
5
Order By: Relevance
“…supplementation of skin lipids, and there's no specific relationship to the fatty acid compositions of each oil. Previous literature shows that formulations containing oil from spent coffee grounds have multiple skin benefits on barrier function and skin hydration [12] when compared to baseline values, corroborating the results obtained in this study.…”
Section: Irritant Potentialsupporting
confidence: 92%
See 2 more Smart Citations
“…supplementation of skin lipids, and there's no specific relationship to the fatty acid compositions of each oil. Previous literature shows that formulations containing oil from spent coffee grounds have multiple skin benefits on barrier function and skin hydration [12] when compared to baseline values, corroborating the results obtained in this study.…”
Section: Irritant Potentialsupporting
confidence: 92%
“…The coffee grounds oil has a predominance of unsaturated fatty acids, including 44.7% linoleic acid [12].…”
Section: Evaluation Of Skin Hydration and Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several published reports, Ribeiro et al 38 ). This outcome revealed that both the creams were effective in elevating the water-holding capacity of the skin.…”
mentioning
confidence: 96%
“…Waste materials can be attractive to use in cosmetics products because of the higher concentration of carbohydrate, proteins and lipids. In this case, a cosmetic product has been developed using spent coffee grounds by Ribeiro et al (2013). Spent coffee lipid extraction was performed by supercritical fluid extraction obtained a yellow viscous oil extract.…”
Section: Botanicals and Natural Products In Cosmeticsmentioning
confidence: 99%